Culture Wars and City Politics, Revisited: Local Councils and the Australia Day Controversy. Issue 1 (January 2022) - Busbridge, Rachel; Chou, Mark
Conflicts rooted in questions of morality and values—so-called "culture wars"—pose difficult questions for local governance. Yet, when it comes to culture wars, local governments can be as politically active as other levels of government. This article explores the role of local government in the culture war surrounding Australia's national holiday, Australia Day. We draw on the pioneering work of Elaine Sharp on urban politics, culture wars, and local government to document and analyze how Australian local governments have responded to the Australia Day controversy. Whereas Sharp's typology is instructive, the ways in which the Australia Day debate has played out at the local level necessitate additional categories of responsiveness. These additional categories may contribute to the broader rejuvenation of studies on culture wars and local politics in light of new fronts in contemporary culture wars and the changing face of local government.